P.056 Combined conventional and amplitude-integrated EEG monitoring in neonates: a prospective study. (5th June 2019) - Buttle, SG; Lemyre, B; Sell, E; Redpath, S; Bulusu, S; Webster, R; Pohl, D
Abstract : Background: Seizure monitoring via amplitude-integrated EEG (aEEG) is standard of care in many NICUs; however, conventional EEG (cEEG) is the gold standard for seizure detection. We compared the diagnostic yield of aEEG interpreted at the bedside, aEEG interpreted by an expert, and cEEG.Methods: Neonates received aEEG and cEEG in parallel. Clinical events and aEEG were interpreted at bedside and subsequently independently analyzed by experienced neonatology and neurology readers. Sensitivity and specificity of bedside aEEG as compared to expert aEEG interpretation and cEEG were evaluated.Results: Thirteen neonates were monitored for an average duration of 33 hours (range 15-94). Fourteen seizure-like events were detected by clinical observation, and 12 others by bedside aEEG analysis. None of the bedside aEEG events were confirmed as seizures on cEEG. Expert aEEG interpretation had a sensitivity of 13% with 46% specificity for individual seizure detection (not adjusting for patient differences), and a sensitivity of 50% with 46% specificity for detecting patients with seizures.Conclusions: Real-world bedside aEEG monitoring failed to detect seizures evidenced via cEEG, while misclassifying other events as seizures. Even post-hoc expert aEEG interpretation provided limited sensitivity and specificity. Considering the poor sensitivity and specificity of bedside aEEG interpretation, combined monitoring may provide limited clinical benefit.